ANALISIS PRICE EARNING RATIO DALAM PENILAIAN HARGA SAHAM DAN BEBERAPA FAKTOR YANG MEMPENGARUHINYA PADA PERUSAHAAN ASURANSI YANG GO PUBLIC DI BURSA EFEK JAKARTA - KHAMDAN RIFA'I, 099511866 (1998)
The results show that. first. independet variabels have significant effect on PER amount simultaneously. Second, variabel of earning growth level per share has quite significant effect on price earning ratio amount in share price valuation of insurance company. Third, there is no difference between market PER and PER of each go public insurance company in Jakarta Stock Exchange, fourth. There is difference between market share price and share price of go public insurance company in Jakarta Stock Exchange.